New benzimidazole derivatives as antimycobacterial agents - Klimesová, Vera; Kocí, Jan; Waisser, Karel; Kaustová, Jarmila (Farmaco (Societa chimica italiana, 2002)
A set of 2-alkylsulfanyl derivatives of 5-methylbenzimidazole was synthesized and evaluated for antimycobacterial activity. The structures of the compounds were confirmed by 1H NMR and IR data, and their purity by elemental analysis. Antimycobacterial activities against Mycobacterium tuberculosis and nontuberculous mycobacteria were expressed as the minimum inhibitory concentration. The substances exhibited significant antimycobacterial activity, in particular against both strains of Mycobacterium kansasii. The effect of the most active compound in the set, 3,5-dinitro derivative 3t, exceeded that of the standard isoniazide against M. kansasii and Mycobacterium avium.
Keywords: benzimidazoly; Benzimidazoles; vztahy mezi strukturou a aktivitou; Spectrophotometry, Infrared; Mycobacterium; Structure-Activity Relationship; magnetická rezonanční spektroskopie; Microbial Sensitivity Tests; Magnetic Resonance Spectroscopy; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; spektrofotometrie infračervená